2020
DOI: 10.7150/jca.45190
|View full text |Cite
|
Sign up to set email alerts
|

ZNF521 which is downregulated by miR-802 suppresses malignant progression of Hepatocellular Carcinoma through regulating Runx2 expression

Abstract: Zinc finger protein 521 (ZNF521) plays an important role in the tumor development and process. However, its regulatory role in hepatocellular carcinoma (HCC) remains unclear. In this study, we demonstrated for the first time that ZNF521 mRNA and protein was down-regulated in HCC tissues and cell lines. Down-regulated ZNF521 expression was significantly associated with malignant prognostic features, including advanced TNM stage and large tumor size. For 5-year survival, ZNF521 served as a potential prognostic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…In vitro experiments also further showed that miR-802 promoted the proliferation of lung cancer cells. 35 The abnormal expression of miR-802 has been confirmed in the tumor tissues or tumor cells of 15 cancers, including TSCC, 4 OSCC, 5,6 LSCC, 8 GC, [9][10][11] CRC, [12][13][14] PC, [30][31][32] HCC, [22][23][24][25] PCa, 2,33 bladder urothelial cancer, 26 BC, 15,16 CC, [17][18][19] EOC, 20 lung cancer, [34][35][36] osteosarcoma, 27,28 and melanoma. 21 To note, the abnormal expression of miR-802 in ESCC 7 and cholesteatoma 29 has only been confirmed in tumor cells.…”
Section: Ab Err Ant E Xpre Ss I On Of Mir-8 0in Tumor Smentioning
confidence: 99%
“…In vitro experiments also further showed that miR-802 promoted the proliferation of lung cancer cells. 35 The abnormal expression of miR-802 has been confirmed in the tumor tissues or tumor cells of 15 cancers, including TSCC, 4 OSCC, 5,6 LSCC, 8 GC, [9][10][11] CRC, [12][13][14] PC, [30][31][32] HCC, [22][23][24][25] PCa, 2,33 bladder urothelial cancer, 26 BC, 15,16 CC, [17][18][19] EOC, 20 lung cancer, [34][35][36] osteosarcoma, 27,28 and melanoma. 21 To note, the abnormal expression of miR-802 in ESCC 7 and cholesteatoma 29 has only been confirmed in tumor cells.…”
Section: Ab Err Ant E Xpre Ss I On Of Mir-8 0in Tumor Smentioning
confidence: 99%
“…Compared to pancreatic cancers, hepatocellular carcinomas (HCC) express high miR-802, which is up-regulated compared to adjacent, non-tumor tissues. In 2020, Yang et al [35] demonstrated that ZNF521 expression was abnormally down-regulated by miR-802 both in HCC tissues and liver cancer cell lines resulting in a malignant progression of the tumor. It was demonstrated by transcription reporter assays that miR-802 was physically involved in regulating ZNF521 expression binding to the miR-802 site in the 3 UTR of ZNF521 in HCCs.…”
Section: Interplay Between Mirnas and Znf521 In Pancreatic And Liver Cancermentioning
confidence: 99%
“…In addition, it was shown in HCC cells that ZNF521, acting as a co-transcriptional repressor, binding Runx2 [36] and inhibiting its transcriptional activity involving PI3K/AKT signaling, blocks the tumor progression [35]. Runx2 is a bone-specific transcriptional regulator required during embryogenesis for skeletal development and is the main marker of osteoblastic differentiation [37,38]; the mouse protein, Zfp521, is able to bind Runx2 and antagonize its transcriptional activity, thereby controlling osteoblast differentiation from mesenchymal stem cells in vitro [39].…”
Section: Interplay Between Mirnas and Znf521 In Pancreatic And Liver Cancermentioning
confidence: 99%
See 2 more Smart Citations